Ruwat Islami: Islamic dialectics and culture in Java, Indonesia - Edi Nurhidin; Abad Badruzaman (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
This paper studies the Islamic ruwat tradition as a manifestation of the encounter between Islam and local culture in Java within the framework of the Islam Nusantara discourse. This study begins with a literature survey enriched with qualitative field research. Informants in this research are religious leaders as well as community leaders who have knowledge and experience about ruwatan. The data that has been collected is then analyzed qualitatively according to the research focus. The results of this study found that an ruwat islami tradition is a form of harmonization between Islamic teachings and Javanese culture that is still sustainable today. The practice of ruwat islami rituals requires various types of dishes (sajen) as a form of alms that contain symbolic meanings in the form of Islamic values, teachings/doctrines, and history. The meeting point between the two resulted in the ruwat islami tradition which is one of the heritage of the Islam Nusantara tradition.